Using energy balance method to study the thermal behavior of PV panels under time-varying field conditions. (1st November 2018) - Aly, Shahzada Pamir; Ahzi, Said; Barth, Nicolas; Abdallah, Amir
Highlights: 1-D finite difference-based fully transient thermal model developed for PV panels. The model uses realistic boundary conditions and physical heat transfer mechanisms. Model validated against PV panel's datasheet information and field experiments. Model compared to existing analytical, empirical and numerical thermal models. The developed model performs better than existing models, in all the test criteria. Abstract: A precise estimate of PV panels temperature is crucial for accurately assessing their electrical performance. Therefore, in this study, one of the main aims has been to significantly improve the prediction accuracy of the PV cell temperature, by using realistic boundary conditions. Unlike previous thermal models in the literature, which usually focus on its mere application, a detailed step by step development and numerical implementation of the complete model has also been provided in great details in this work. The developed model is transient, so it can fully simulate the thermal performance of any PV panel under time-varying field conditions. Once the model is defined for a specific PV panel, the only external inputs it needs are the total incident solar irradiation, wind speed and the ambient temperature. The model has been adequately validated through PV panel's datasheet provided information, literature data and against a versatile set of experimental data under various weather conditions. After thorough validations, the developed model was compared to various other widely used empirical, analytical and numerical thermal models from the literature. The comparison shows that by using realistic boundary conditions, the developed thermal model has far better prediction accuracy than other models from the literature. The methodology presented in this study is completely generic. That is, though it has been implemented and validated here for a silicon-based PV module the approach may be used to model any free-standing plane PV surface, with appropriate modifications to layer thicknesses and material properties. A range of weather conditions may also be accommodated.